“Out With the Galleries, Out with the Sellouts:” Arts Organizations and Real Estate Investment in Los Angeles and Detroit - Aaron Shkuda (European Journal of American Studies)
Activists in Los Angeles’ Boyle Heights neighborhood have targeted art galleries as a way to protest the area’s gentrification, while Detroit artist Tyree Guyton has drawn praise for his use of connections with local art galleries to broaden the economic impact of his Heidelberg Project. Why were art galleries criticized for their role in gentrifying Los Angeles, while an arts organization in Detroit was lauded for the way it directed capital investment into a disinvested area of the city? To fully understand the relationship between art and capital in an urban context, one must analyze the specific ways in which art brings capital into a neighborhood within the context of the historic, economic, and the policies that shape neighborhood dynamics. Art is often a metonym for capital, and these case studies demonstrate how the symbolic function of the arts can obscure the precise relationships between art and real estate investment.